De novo testicular tissue generation from non-testicular cell lines, biologic and synthetic scaffolds: Current findings and future translational applications - Hosseini, Helia; DeBenedetto, Christina; Eleswarapu, Sriram V.; Ng, Gladys; Sturm, Renea M. (Frontiers in Cell and Developmental Biology, 2022)
In recent decades, reproductive science has revolutionized the options for biological parenthood for the 20 to 50% of infertility cases affected by male factors. However, current solutions exclude those who have are infertile due to absent testicular tissue. This includes anorchic 46,XY individuals due to trauma or congenital factors and transgender men with a 46,XX genotype. There is a clinical need for methods to restore testicular function independent of pre-existing testicular tissue. This mini-review analyzes studies that have applied non-testicular cell lines to generate germline and non-germline testicular parenchymal components. While only 46,XY cell lines have been evaluated in this context to date, the potential for future application of cell lines from 46,XX individuals is also included. Additionally, the role of varied culture methods, media supplementation, and biologic and synthetic scaffolds to further support testicular parenchyma generation are critiqued. De novo testicular tissue generation in this manner will require a focus on both cellular and environmental aspects of tissue engineering. Put together, these studies highlight the future potential for expanded clinical reproductive and endocrine management options for individuals who are currently excluded from aspects of biologic reproduction most consistent with their gender identity and reproductive preferences.